2011
DOI: 10.2460/javma.238.7.922
|View full text |Cite
|
Sign up to set email alerts
|

Use of a duodenal serosal patch in the repair of a colon rupture in a female Solomon Island eclectus parrot

Abstract: Case Description-A 444-g (0.98-lb) 4-year-old sexually intact female Solomon Island eclectus parrot (Eclectus roratus solomonensis) was referred and evaluated for a suspected colonic obstruction. Clinical Findings-The parrot had a 3-day history of not passing feces and lack of appetite following treatment of dystocia that included percutaneous collapse of the egg and manual removal of egg fragments via the cloaca. During this procedure, a tear in the cloacal mucosa developed. The tear was repaired via a midlin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Birds do not have an omentum; thus, use of a serosal patch can be a viable alternative in birds. 21 The serosal patch has been described for cases in which a duodenal defect could not be closed primarily due to risk of luminal compromise. 9,11,22 Its use has been expanded for reinforcement of intestinal closures where either the suture line is of questionable viability or the abdominal environment is nonconducive to healing.…”
Section: Discussionmentioning
confidence: 99%
“…Birds do not have an omentum; thus, use of a serosal patch can be a viable alternative in birds. 21 The serosal patch has been described for cases in which a duodenal defect could not be closed primarily due to risk of luminal compromise. 9,11,22 Its use has been expanded for reinforcement of intestinal closures where either the suture line is of questionable viability or the abdominal environment is nonconducive to healing.…”
Section: Discussionmentioning
confidence: 99%
“…. Serosal patching has being described as a well succeeded supplemental technique when employed to different organs and species 1,5,8,[10][11][12][13][14][15][16][18][19][20] . However, one study showed that the use of a serosal patch over intestinal anastomosis did not increase the survival of dogs with peritonitis, when compared to individuals that did not receive such supplementation 15 .…”
Section: Discussionmentioning
confidence: 99%